Recruitment, screening, and baseline participant characteristics in the WALK 2.0 study: A randomized controlled trial using web 2.0 applications to promote physical activity - Caperchione, C. M.; Duncan, M. J.; Rosenkranz, Richard R.; Vandelanotte, C.; Van Itallie, A. K.; Savage, T. N.; Hooker, C.; Maeder, A. J.; Mummery, W. K.; Kolt, G. S. (My University, 2016)
Objective To describe in detail the recruitment methods and enrollment rates, the screening methods, and the baseline characteristics of a sample of adults participating in the Walk 2.0 Study, an 18 month, 3-arm randomized controlled trial of a Web 2.0 based physical activity intervention. Methods A two-fold recruitment plan was developed and implemented, including a direct mail-out to an extract from the Australian Electoral Commission electoral roll, and other supplementary methods including email and telephone. Physical activity screening involved two steps: a validated single-item self-report instrument and the follow-up Active Australia Questionnaire. Readiness for physical activity participation was also based on a two-step process of administering the Physical Activity Readiness Questionnaire and, where needed, further clearance from a medical practitioner. Results Across all recruitment methods, a total of 1244 participants expressed interest in participating, of which 656 were deemed eligible. Of these, 504 were later enrolled in the Walk 2.0 trial (77% enrollment rate) and randomized to the Walk 1.0 group (n = 165), the Walk 2.0 group (n = 168), or the Logbook group (n = 171). Mean age of the total sample was 50.8 years, with 65.2% female and 79.1% born in Australia. Conclusion The results of this recruitment process demonstrate the successful use of multiple strategies to obtain a diverse sample of adults eligible to take part in a web-based physical activity promotion intervention. The use of dual screening processes ensured safe participation in the intervention. This approach to recruitment and physical activity screening can be used as a model for further trials in this area. © 2016 The Authors.
Citation: Caperchione, C. M., Duncan, M. J., Rosenkranz, R. R., Vandelanotte, C., Van Itallie, A. K., Savage, T. N., . . . Kolt, G. S. (2016). Recruitment, screening, and baseline participant characteristics in the WALK 2.0 study: A randomized controlled trial using web 2.0 applications to promote physical activity. Contemporary Clinical Trials Communications, 2, 25-33. doi:10.1016/j.conctc.2015.12.004
Keywords: Internet; Physical Activity; Randomized Controlled Trial; Recruitment; Screening; Accelerometer